Application of Supercritical CO2 Extraction and Identification of Polyphenolic Compounds in Three Species of Wild Rose from Kamchatka: Rosa acicularis, Rosa amblyotis, and Rosa rugosa - Mayya P. Razgonova; Muhammad A. Nawaz; Elena A. Rusakova; Kirill S. Golokhvast (Plants)
A comparative metabolomic study of three varieties of wild Rosa (Rosa acicularis, Rosa amblyotis, and Rosa rugosa) from a Kamchatka expedition (2024) was conducted via extraction with supercritical carbon dioxide modified with ethanol (EtOH), and detection of bioactive compounds was realized via tandem mass spectrometry. Several experimental conditions were investigated in the pressure range 50–350 bar, with the used volume of co-solvent ethanol in the amount of 2% in the liquid phase at a temperature in the range of 31–70 °C. The most effective extraction conditions are the following: pressure 200 Bar and temperature 55 °C for Rosa acicularis; pressure 250 Bar and temperature 60 °C for Rosa amblyotis; pressure 200 Bar and temperature 60 °C for Rosa rugosa. Three varieties of wild Rosa contain various phenolic compounds and compounds of other chemical groups with valuable biological activity. Tandem mass spectrometry (HPLC-ESI–ion trap) was applied to detect the target analytes. A total of 283 bioactive compounds (two hundred seventeen compounds from the polyphenol group and sixty-six compounds from other chemical groups) were tentatively identified in extracts from berries of wild Rosa. For the first time, forty-eight chemical constituents from the polyphenol group (15 flavones, 14 flavonols, 4 flavan-3-ols, 3 flavanones, 1 phenylpropanoid, 2 gallotannins, 1 ellagitannin, 4 phenolic acids, 1 dihydrochalcone, and 3 coumarins) were identified in supercritical extracts of R. acicularis, R. amblyotis, and R. rugosa.